Food and Self in Aimee Bender’s The Particular Sadness of Lemon Cake and Judith M Fertig’s The Cake Therapist - Lal J, Lekshmi; Nair, Aathira M; K V, Aswathy Das; K V, Aswathy Das (International Journal of Psychosocial Rehabilitation, 2020)
The paper aims to locate the presence of Food and Self in Aimee Bender’s “The Particular Sadness of Lemon Cake” and Judith M Fertig’s ‘The Cake Therapist.’ Aimee Bender is an American short story writer and novelist, celebrated for her surreal plots and Judith M Fertig is an award winning cook book author. The Cake Therapist is her debut novel. The novels explore the connection between food and personal identity. The novels portray the protagonists’ journey from awareness to self- discovery through food. Food is the central theme in both the novels. Food is used as a metaphor in literary texts because of its universality. The novels abound in magical menus and gastronomic metaphors which engage all senses of the readers. In the novels, an analysis of a character’s attitude towards food reveals their identity.